A diet-induced obese and diabetic host phenotype reduces mosquito ZIKV infections and remodels gut metabolism - Menezes, Alexandre; Walter-Nuno, Ana Beatriz; Costa-Bartuli, Emylle; Moreira, Daniel; El-Bacha, Tatiana; Méndez, Ana Paula; Amarante, Anderson; Kistenmacker, Nathan; Huaman, Pâmela; Busch, Mileane; Pereira, Jéssica; Ramos, Isabela; et al. (Frontiers in Immunology, 2025)
IntroductionArbovirus infections, including dengue, Zika, and chikungunya, constitute significant global health threats. The epidemiology of these diseases is closely tied to the biology and ecology of the mosquito Aedes aegypti, particularly regarding its vector competence—the mosquito’s ability to acquire, maintain, and transmit pathogens. While genetic variations among mosquito populations have traditionally received the most attention and are often regarded as the main determinants of vector competence, life history components, including immune history, microbiota composition, and nutritional status, are increasingly recognized as critical modulators of this trait. In this context, the increasing prevalence of diet-induced obesity and diabetes in human hosts—a condition that alters blood plasma composition—may reshape the mosquito´s nutritional and immunological landscape.MethodsThis study investigated the impact of these conditions on A. aegypti biology and Zika virus (ZIKV) infection. For this, AG129 mice were fed a high-fat, high-sucrose (HFHS) diet for 20 weeks to develop weight gain and insulin resistance. By comparing mosquitoes fed on healthy and diabetic-obese mice, we assessed changes in life history traits, immunometabolic parameters, and transcriptomic profiles.ResultsNotably, mosquitoes fed on HFHS-fed mice showed reduced survival, altered lipid profile and a significant reduction in midgut and systemic ZIKV infection levels, which correlated with distinct transcriptomic alterations in genes related to gut metabolism and homeostasis.DiscussionThese findings demonstrate that the host’s metabolic state is a critical modulator of mosquito physiology, increasing mosquito mortality while reducing ZIKV infection levels. This highlights that host-centric factors, such as the rising prevalence of metabolic syndrome, are an overlooked variable that may have complex epidemiological consequences for arbovirus transmission by mosquitoes.